Penetapan Kadar Vitamin C Secara Iodimetri Pada Paprika Hijau (Capsicum annuum L. Var. Grossum) Yang Tumbuh Disekitar Gunung Sinabung Setelah Erupsi - Ginting, Ferdinand Paulus; Sembiring, Evarina; br Brahmana, Nettietalia; Nurazizah (Universitas Sari Mutiara Indonesia, 2022)
Vitamin C is found in many fruits and vegetables, one of which is chilies and peppers. Paprika is thought to have the highest vitamin C content among other types of chili. This study aimed to determine vitamin C levels in green bell peppers (Capsicum annuum L. Var. Grossum) which grew around Mount Sinabung exposed to eruptions and green peppers that grew. far from Mount Sinabung which was not affected by the eruption Compared with the literature the content of vitamin C in fresh green bell peppers is 120 mg/100 g. The method used was an iodometric quantitative analysis method to determine vitamin C levels. The standard solution used was sodium thiosulfate 0 solution. .1 N and the titer solution used was 0.1 N iodine solution. The results of the determination of vitamin C levels in green peppers growing around Mount Sinabung which were affected by the eruption using quantitative analysis methods obtained levels of 104.67 mg/100 g and Green peppers growing far from Mount Sinabung that were not affected by the eruption were found to be 113.71 m g/100 g. The results of the study concluded that both samples experienced a decrease, from the original vitamin C content of fresh green peppers, which was 120 mg/100 g. This is caused by exposure to volcanic ash and hot steam generated by Mount Sinabung.